Instrumentation, metrology, and standards for nanomanufacturing II : 10 August 2008, San Diego, California, USA - Postek, Michael T.; Allgair, John A. (John Alexander); Society of Photo-Optical Instrumentation Engineers (Washington : SPIE, 2008)
09